2019
DOI: 10.1590/1807-1929/agriambi.v23n11p826-832
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen management, cultivars and growing environments on wheat grain quality

Abstract: The aim of this study was to evaluate the influence of nitrogen (N) fertilization, environment and cultivars on the protein concentration, sodium dodecyl sulfate sedimentation test (SDSS) volume and falling number in wheat. The experimental design was a randomized blocks in split plot scheme with four repetions. Four wheat genotypes were evaluated under six N managements in four enviroment (subplots). The wheat genotypes evaluated were IPR Catuara TM, BRS Gaivota, Quartzo and CD 120. Protein concentration, SDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Previous studies found that amylopectin was more vulnerable to soil moisture content and reducing irrigation amount appreciably increased amylopectin content [ 140 ]. Therefore, suitable irrigation amount was beneficial to starch accumulation and yield formation of wheat [ 141 ]. It was also found that the total starch content and amylose content of maize increased with the increases in irrigation times with reasonable irrigation amount, whereas both amylose and amylopectin decreased under either severe drought or water-logging conditions [ 142 ].…”
Section: Effects Of Irrigation Management On Wheat Grain Qualitymentioning
confidence: 99%
“…Previous studies found that amylopectin was more vulnerable to soil moisture content and reducing irrigation amount appreciably increased amylopectin content [ 140 ]. Therefore, suitable irrigation amount was beneficial to starch accumulation and yield formation of wheat [ 141 ]. It was also found that the total starch content and amylose content of maize increased with the increases in irrigation times with reasonable irrigation amount, whereas both amylose and amylopectin decreased under either severe drought or water-logging conditions [ 142 ].…”
Section: Effects Of Irrigation Management On Wheat Grain Qualitymentioning
confidence: 99%
“…The abovementioned compositional factors, as substantial dimensions of cereal grain quality are strongly affected by the genetic potential, the growing environment and agricultural practices [12,13]. Among agronomic practices, key strategies include cultivar selection [14]; water regimes [15]; nutritional status, especially N utilization [8]; and edaphic and climatic conditions, in particular, temperature changes due to year, location and planting date [16]. The effect of these factors on grain quality is more complex than yield.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between nitrogen application and alpha-amylase activity is complex and context-dependent [45]. Excessive nitrogen, especially if applied late in the growing season, can increase the risk of pre-harvest sprouting and affect enzyme activity [46]. Moreover, grain falling can be affected by weather conditions.…”
Section: Grain Falling Number and Sedimentation Indexmentioning
confidence: 99%